Exploring IL-17 in spondyloarthritis for development of novel treatments and biomarkers - Groen, Solveig Skovlund; Sinkeviciute, Dovile; Bay-Jensen, Anne Christine; Thudium, Christian S.; Karsdal, Morten A.; Thomsen, Simon Francis; Schett, Georg; Nielsen, Signe Holm (Autoimmunity Reviews, 2021)
Spondyloarthritis (SpA) is an umbrella term describing a family of chronic inflammatory rheumatic diseases. These diseases are characterised by inflammation of the axial skeleton, peripheral joints, and entheseal insertion sites throughout the body which can lead to structural joint damage including formation of axial syndesmophytes and peripheral osteophytes. Genetic evidence, preclinical and clinical studies indicate a clear role of interleukin (IL)- 23 and IL-17 as mediators in SpA pathogenesis. Targeting the IL-23/−17 pathways seems an efficient strategy for treatment of SpA patients, and despite the remaining challenges the pathway holds great promise for further advances and improved therapeutic opportunities. Much research is focusing on serological markers and imaging strategies to correctly diagnose patients in the early stages of SpA. Biomarkers may facilitate personalised medicine tailored to each patient's specific disease to optimise treatment efficacy and to monitor therapeutic response. This narrative review focuses on the IL-17 pathway in SpA-related diseases with emphasis on its role in pathogenesis, current approved IL-17 inhibitors, and the need for biomarkers reflecting core disease pathways for early diagnosis and measurement of disease activity, prognosis, and response to therapy.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Biomarker; IL-17; pathogenesis; Spondyloarthritis; treatment